Philosophy and male domination. Enrique Dussel and Richard Rorty’s critical reflections - Figueroa Muñoz, Maximiliano (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article develops E. Dussel’s and R. Rorty’s critical reflections on the prevailing gender domination. The main parts of the article are: an introduction on male domination as a cultural paradigm, an outline of the traditional position of philosophy with regard to this paradigm, taking Nietzsche as an example, and a presentation of the reflections of Dussel’s philosophy of liberation and Rorty’s neopragmatism aimed at overcoming this paradigm —reflections that are structured as an erotic of liberation and as an anti-essentialist and anti representationalist perspective, respectively.